Interpersonal behaviour styles of primary education teachers during science lessons - Fisher, Darrell; den Brok, P.; Waldrip, B.; Dorman, J. (2011)
This study reports the first development in Australia of primary science teacher typologies of teacher–student interpersonal behaviour, which was measured by students’ perceptions using the Questionnaire on Teacher Interaction (QTI). Earlier work with the QTI in The Netherlands has revealed eight different interpersonal styles, which were later confirmed with an American sample of secondary-school teachers and which were similar to types found with Australian secondary-school science teachers. The present study investigated the extent to which typologies found in earlier studies also apply to primary teachers. A cluster analysis was used to determine Australian typologies and to compare these with earlier findings. Prior typologies could only be partially confirmed, and the found typology of six styles was able to explain variance in both student outcomes and perceptions of cultural elements of the learning environment.